Cancer screening among adults with and without serious mental illness: a mixed methods study - Murphy, Karly A. (Med Care, 2021)
BACKGROUND: Persons with serious mental illness (SMI) die 10–20 years earlier than the general population; cancer is the second leading cause of death. Differences in cancer screening between SMI and the general population are not well understood. OBJECTIVES: To describe receipt of cancer screening among individuals with versus without SMI and to explore clinicians’ perceptions around cancer screening for people with SMI. METHODS: Mixed-methods study using 2010–2017 MarketScan commercial insurance administrative claims data and semi-structured clinician interviews. In the quantitative analyses, we used multivariate logistic regression analyses to calculate the likelihood of receiving cervical, breast, colorectal, or prostate cancer screening among people with versus without SMI, defined as schizophrenia or bipolar disorder. We conducted semi-structured interviews with 17 primary care physicians and 15 psychiatrists. Interview transcripts were coded using a hybrid deductive/inductive approach. RESULTS: Relative to those without SMI, individuals with SMI were less likely to receive screening for cervical cancer (adjusted Odds Ratio [aOR] 0.80; 95% CI:0.80–0.81), breast cancer (aOR 0.79; 95% CI:0.78–0.80), colorectal cancer (aOR 0.90; 95% CI:0.89–0.91), and prostate cancer (aOR 0.85; 95% CI:0.84–0.87). Clinicians identified five themes that may help explain the lower rates of cancer screening in persons with SMI: access to care, available support, prioritization of other issues, communication, and patient concerns. CONCLUSIONS: People with SMI were less likely to receive four common types of cancer screening. Improving cancer screening rates in the SMI population will likely require a multi-disciplinary approach to overcome barriers to screening.